DAMPAK LOGAM BERAT TERHADAP PERUBAHAN POLIMORFISMEIKAN BADUKANG (Arius sp.) DI ESTUARIA MUARA SUNGAI KAHAYAN DAN KATINGAN KALIMANTAN TENGAH [Impact of heavy metals on polymorphism changes of catfish {Arius sp.) in estuaries of Kahayan and Katingan Rivers, - Edison Harteman; Dedi Soedharma; Adi Winarto; Harpasis S. Sanusi (Jurnal Iktiologi Indonesia, 2007)
The purpose of this study was to evaluate impact of metal pollutants: Pb, Cd, and Hg on morphism changes of fish phenotype through concentration and bio-concentration factor (BCF). The study site was located in the river mouths of Kahayan River and Katingan River. Samples collected were water sample and fish sample with malformation on pectoral and caudal hard fin rays. Water sample and fish bone were analysed by Atomic Absorption Spectrophotometer (AAS). The results indicated that lead (Pb) concentration in the estuary and in pectoral and caudal hard fin rays was the highest compared to cadmium (Cd) and mercury (Hg) concentration. It may because Cd and Hg have high affinity to bone tissue of pectoral and caudal hard fin rays than Pb. The highest lead concentration in the water could cause high its metal in bone tissue. If metal in river mouth has not detected or low concentration than standard values of water and biota, it does not mean the water safe to fish and other aquatic organism because heavy metal has been continuously accumulated in tissue. Pb, Cd and Hg have ability to replace Calcium in Phosphate of cell of pectoral and caudal fins. This causes inhibited Ca absorption into bone cell. As consequence, chemical composition on bone changes the bone experiences softening inhibited hardening, and malformation. Bone malformation was caused by changes of bone chemical composition and environmental effects.